WM capacity and temporal attention. Could orienting attention to a selective point in time influence WM capacity? - Vranić, Andrea; Tonković, Mirjana (2005)
Aim. "Temporal attention" can be defined as a process aimed at allocating brain resources on the predicted onset of an incoming event. Temporal certainty in the cue-target relation was shown to improve reaction time, possibly due to an increase of alertness/vigilance. The aim of the present experiment was to investigate if this temporal certainty can be used to modulate working memory capacity. Method. Thirty-five subjects participated in the study. Experimental task was a standard working memory task combining sentence verification and its final word recall. An S1– S2 paradigm was used in which a warning stimulus (S1- brief light) provided information on the duration of the time interval (foreperiod) preceding an imperative stimulus (S2 – stimulus sentence). There were three conditions: no warning signal (control), short foreperiod (SOA=500ms), long foreperiod (SOA=1500ms). Control condition measured baseline WM capacity. Their order was counterbalanced across subjects. Results. An attentional effect was found with a shorter sentence verification time for plausible versus implausible sentences. Final word recall (WM span) also improved when warning signal was introduced. A trend of differential effect of the length of the foreperiod on the two aspects of the experimental task was observed. Conclusion. Findings suggest that subjects were capable of using temporal information to deploy attentional resources. Selective information about temporal intervals can be used dynamically to enhance working memory performance. It seems that selective attention modifies different levels of stimulus analysis (perceptual versus cognitive response-related) according to whether spatial or temporal information is available.
Projekt MZOS
ENG